Is Fairly Priced Deposit Insurance Possible? - Chan, Yuk-Shee; Greenbaum, Stuart I; Thakor, Anjan V (Journal of Finance, 1992)
The authors analyze risk-sensitive, incentive-compatible deposit insurance in the presence of private information and moral hazard. Without deposit-linked subsidies, it is impossible to implement risk-sensitive, incentive-compatible deposit insurance pricing in a competitive, deregulated environment except when the deposit insurer is the least risk averse agent in the economy. The authors establish this formally in the context of an insurance scheme in which privately informed depository institutions are offered deposit insurance premia contingent on reported capital; the result holds for alternative sorting instruments as well. This suggests a contradiction between deregulation and fairly priced, risk-sensitive deposit insurance.